A Scoping Review on Digital Interventions in Mental Health in Nepal (Journal of Psychiatrists' Association of Nepal, 2026)
Background: Digital interventions for mental health are gaining popularity in Nepal. They help address barriers to treatment seeking for mental health concerns and are one of the possible solutions for addressing the mental health treatment gap in Nepal. Given the impact digital interventions can have on the management of mental and substance use disorders, we have conducted this review with theaim of assessing the existing literature on digital interventions for mental health problems in Nepal.Material and methods: We conducted a literature search for original research studies that have explored digital intervention in Nepal till December 2025 in three databases (PubMed, SCOPUS, PsycINFO ). The reference lists of all articles were searched for any studies not retrieved by the electronic search.Results: Out of 91 studies, 17 (18.7%) were included after exclusions. Eight studies (47%) were qualitative, four (24%) were pilot studies, and three (18%) were retrospective chart reviews. Twelve studies (70.5%) used teleconsultation, mainly synchronous (N=6, 35.3%) as a mode of digital intervention.Conclusion: There has been emerging but limited research on digital mental health interventions in mental health in Nepal. They hold substantial promise for improving access, capacity building, scalability, and quality of care, and treatment outcomes across various health systems in Nepal. Their successful implementation requires a comprehensive approach addressing digital literacy, digital divide, and systemic barriers. Strengthening of the evidence is essential through robust research, and use of contextually relevant interventions in diverse and underrepresented populations is necessary. There is a need for collaboration between multiple stakeholders to attain this goal.